Mitochondrial DNA deletions accurately detect endometriosis in symptomatic females of child-bearing age. (15th January 2019) - Creed, Jennifer; Maggrah, Andrea; Reguly, Brian; Harbottle, Andrew
Aim: Accurate noninvasive diagnostic aids for endometriosis are needed. We evaluated mitochondrial DNA deletions as potential biomarkers for endometriosis.Methods: The diagnostic accuracy of deletions was evaluated by quantitative polymerase chain reaction (QPCR) using well-characterized clinical specimens from all subtypes and stages of endometriosis in a case–control format (n = 182).Results: Deletions (1.2 and 3.7 kb) detected in blood differentiated between endometriosis and controls (area under the curve [AUC] 0.71–0.90). Differences in deletion levels were statistically significant (p < 0.05) for all disease subtypes and stages. Neither deletion was correlated with patient or specimen age or hormone status. The 1.2 kb deletion was not correlated with menstrual stage; the 3.7 kb deletion was significantly correlated between two of the groups.Conclusion: Biomarkers of the mitochondrial genome, including the deletions described here, offer a promising and largely unexplored avenue in the pursuit of diagnostic markers for endometriosis that can be effectively translated to clinical application.